Exploring the Student Critical Thinking in Mathematical Problem Solving - Rochaminah, Sutji; ‎ , Irmawati; Rizal, Muh. (KnE Social Sciences, 2025)
This research qualitative aims to describe students’ critical thinking in solving sequences and series. The research participants were 3 students from grade VIII, selected based on the results of their math tests. Data were collected by giving the task of solving problems and interviews. The student’s critical thinking is described using the approach focus, reason, inference, clarity, and overview (FRISCO). The results showed that participants with high math skills can identify the main problem, analyzing questions and statements, reasoning of inductive and assessing the difference was the same, concluding the value of the difference and the solution, making pattern of sequence, and determining the sum of the first 12 terms using the arithmetic series formula, explaining the terms and symbols used in the formula, solving the problem again by adding up each term and comparing the results with the previous results. Participant with moderate mathematical ability wrote down relevant information, using inductive reasoning and mathematical principles and did not use arithmetic series formula, concluding the value of the difference and the solution, making sequence pattern, determining the sum of the first 12 terms by add up each, explaining the term and the difference symbol. Participant with low math ability, only wrote down and mentioned what is known and asked and gave reasons using question marks for question sentences. The description of critical thinking can be considered by teachers in formulating learning strategies for critical thinking.